AWARENESS LEVEL OF STREET FOOD VENDORS ON CODE OF HYGIENE PRACTICE FOR STREET VENDED FOODS, KARU LOCAL GOVERNMENT AREA, NASARAWA STATE, NIGERIA - C.E., Amfani- Joe, (IJRDO - Journal of Applied Management Science, 2017)
This study assessed the awareness level of street food vendors on the code of hygiene practice for street vended foods in Karu Local Government Area of Nasarawa State. The survey research design was adopted for the study. It examined the economic activities, constraints to access of information by street food vendors, satisfaction of street food vendors with performance of the food safety agencies and, their awareness of the code of hygiene practice for street vended foods on a five point Likert scale. The demographic characteristics were the independent variable. The chronbach alpha reliability of the instrument was determined at 0.973. An awareness index was adopted in constructing the questionnaire and validated. The statistics used for the analysis of variance t-test and multi-nominal logistic regression. Results revealed that [4.3%] males compared to [23.7%] females had knowledge of code of hygiene practice for street vended food. Observed chi-square test showed the test is 9.089 with a value of 0.03 [P<0.05] indicating that gender plays significant role in food safety practice. There was no significant association in level of awareness of food safety practice by age as the observed chi-square test of 33.046 and the P value [P<0.05] was determined, while the ages of vendor and above 39yrs [11.0%] showed that this age bracket could be a significant factor of their awareness of obligatory registration of food business premises. Education attainment significantly associated will vendor’s awareness of food safety practices and control by government as the observed P value for two test give 0.278 and 0.438 ]P>0.05]. Among those who hawk waves only [3.2%] and [29.0%] stationary vendors were aware of code of hygiene practice for street food vendors but not obligatory registration of business premises. Observed relationship between street food vendors and the agencies of government is limited to revenue collection. Most street food vendor’s do not understand written protocols of food safety 142[74.0%] along with 48[25%] said code of hygiene practice if it existed at all was not written in their local languages 158 [82.3%] and 10 [5.2%] of the respondents disagreed and strongly disagreed respectively that they heard of the protocols of food safety from extension workers. It can be concluded that street food vendors were not aware of one code of hygiene practice for street vended foods. The use of minors and their low educational level could have adverse effect on the nation’s development as the potential risk of disease outbreak could be high. It is recommended among others that government agencies keep abreast with and awake to their responsibility to tax payers in executing their duties effectively and efficiently in view of the mandate reposed on them. It is also recommended, however, that further study on a national scale should be conducted to determine the state of affairs on this subject in order to make a generalization for the Nigerian State